The debate on network neutrality regulation: A technological innovation perspective. (21st September 2018) - Yang, Lin; Lin, Xuchen; Lu, Ting‐Jie; Chen, Xia
Summary: In the network neutrality debate, safeguarding innovations in the digital economy is an important concern. However, the impacts of network neutrality regulation on technological innovation in telecommunications have not been well understood, especially with mathematical model. This study first briefly discusses the significant role of technological innovation in telecommunications. Then, we adopt a stylized two‐sided model (Internet broadband provider connect the two sides of Internet, content providers and end customers) and use two‐stage game theory to examine the decision‐making of network operators and content providers in two alternative situations, respectively, that is, the neutral regime and non‐neutral regime. By comparing players' decisions in the two regimes, the impacts of network neutrality regulation on innovations are revealed. We find that non‐neutral regime increases both network infrastructure investments and congestion‐sensitive content innovations. In other words, network neutrality regulation inhibits telecommunications technological innovation and meanwhile hinders the emergence of high‐level content innovation.